Characterization of the mechanism of protection mediated by CS-D7, a monoclonal antibody to Staphylococcus aureus iron regulated surface determinant B (IsdB) - Pancari, Gregory; Fan, Hongxia; Smith, Sharon; Joshi, Amita; Haimbach, Robin; Clark, Desmond; Li, Yingzhe; Hua, Jin; McKelvey, Troy; Ou, Yangsi; Drummond, James; Cope, Leslie; et al. (Frontiers in Cellular and Infection Microbiology, 2012)
We previously reported the development of a human monoclonal antibody (CS-D7, IgG1) with specificity and affinity for the iron regulated surface determinant B (IsdB) of Staphylococcus aureus. CS-D7 mediates opsonophagocytic killing in vitro and protection in a murine sepsis model. In light of recent data indicating that IsdB specific T cells (CD4+, Th17), not Ab, mediate protection after vaccination with IsdB, it is important to investigate the mechanism of protection mediated by CS-D7. The mAb was examined to determine if it blocked heme binding to IsdB in vitro. The mAb was not found to have heme blocking activity, nor did it prevent bacterial growth under in vivo conditions, in an implanted growth chamber. To assess the role of the mAb Fc a point mutation was introduced at aa 297 (CS-D7·N297A). This point mutation removes Fc effector functions. In vitro analysis of the mutein confirmed that it lacked measurable binding to FcγR, and that it did not fix complement. The mutein had dramatically reduced in vitro opsonic OP activity compared to CS-D7. Nonetheless, the mutein conferred protection equivalent to the wild type mAb in the murine sepsis model. Both wild type and mutein mAbs were efficacious in FcγR deletion mice (including both FcγRII−/− mice and FcγRIII−/− mice), indicating that these receptors were not essential for mAb mediated protection in vivo. Protection mediated by CS-D7 was lost in Balb/c mice depleted of C3 with cobra venom factor (CFV), was lost in mice depleted of superoxide dismutase (SOD) in P47phox deletion mice, and as previously reported, was absent in SCID mice (Joshi et al., 2012). Enhanced clearance of S. aureus in the liver of CS-D7 treated mice and enhanced production of IFN-γ, but not of IL17, may play a role in the mechanism of protection mediated by the mAb. CS-D7 apparently mediates survival in challenged mice through a mechanism involving complement, phagocytes, and lymphocytes, but which does not depend on interaction with FcγR, or on blocking heme uptake.